Robust resource allocation algorithm for multicarrier NOMA security communication system - Yu ZHANG; Xiongwen ZHAO; Xiaoqing WANG; Suiyan GENG; Peng QIN; Zhenyu ZHOU (Tongxin xuebao)
To improve the spectrum efficiency and enhance the information security of wireless network, a sum secrecy rate maximization-based robust resource allocation algorithm was proposed for a downlink multicarrier NOMA security communication system.Firstly, the artificial noise (AN) precoding vector was designed to be orthogonal to the legitimate channel, so that the legitimate transmission would not be affected by the AN.Then, considering the constraints of rate requirement of each user and the maximum transmit power of base station, a joint AN precoding, downlink data precoding and subcarrier allocation optimization problem was formulated under eavesdropping channel uncertainties.To solve that non-convex problem, it was decomposed into two joint optimization subproblems: precoding optimization and subcarrier allocation.The former was solved based on S-procedure and block coordinate descent (BCD) algorithm, the latter was solved by dynamic matching theory.Simulation results demonstrate that the proposed algorithm has good robustness and can effectively improve the sum secrecy rate.